2021
DOI: 10.1249/mss.0000000000002790
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Investigation in Plasma from Women with Fibromyalgia in Response to a 15-wk Resistance Exercise Intervention

Abstract: Purpose: Fibromyalgia (FM) is a complex pain condition, and exercise is considered the first option of treatment. Few studies have examined the effect of exercise on molecular mechanisms in FM. The aim of this study was to analyze the plasma proteome in women with FM and healthy controls (CON) before and after 15 wk of resistance exercise. This study further investigated whether clinical and exercises-related outcomes correlated with identified plasma proteins in FM. Methods: Plasma samples from 40 FM/25 CON (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…In the studies that form the basis of the project and use the same methods, we have found marked differences in the protein/inflammation pattern in muscles and plasma at CWP/FM 16 17 33. In the proteomics studies of musculature and plasma, we have been able to identify proteins that with great certainty explain the group affiliation (patient or healthy) (R2: 0.81–0.84)16 17; similar results are obtained with the inflammation panel 15.…”
Section: Discussionsupporting
confidence: 67%
“…In the studies that form the basis of the project and use the same methods, we have found marked differences in the protein/inflammation pattern in muscles and plasma at CWP/FM 16 17 33. In the proteomics studies of musculature and plasma, we have been able to identify proteins that with great certainty explain the group affiliation (patient or healthy) (R2: 0.81–0.84)16 17; similar results are obtained with the inflammation panel 15.…”
Section: Discussionsupporting
confidence: 67%
“…32 Most recently, a series of studies using highthroughput serum and plasma proteomics further revealed a dysregulation of circulating proteome in CWP, especially patients with fibromyalgia (FM), where the most regulated proteins are part of the immune system or known to interact with the immune system. 24,25,30,[68][69][70][71] The data further support a significant correlation between serum and plasma proteome profile and clinical parameters in FM and diabetic neuropathic patients, such as mechanical and thermal pain thresholds, pain intensity, and psychological distress. 3,24,25,68,69 Thus, accumulating evidence suggests that patients with chronic pain may live with systemic chronic inflammation, which could have a role in the genesis of long-lasting painful behaviors.…”
Section: Discussionsupporting
confidence: 64%
“…While most of the above mentioned studies analysing mRNA expression or protein levels of few selected targets in blood samples, some studies [2; 29; 34] expanded the screening of inflammatory molecules with multiplex analysis up to 92 targets where they not only detected significant differences in multiple inflammatory biomarkers, but also observed that among patients whose pain and other clinical relevant symptoms improve, most of inflammation related proteins tend to be normalized [29]. Most recently, a series of studies using high-throughput serum/plasma proteomics further revealed a dysregulation of circulating proteome in CWP, especially fibromyalgia (FM) patients, where the most regulated proteins are part of the immune system or known to interact with the immune system [21; 22; 27; 6467]. The data further support a significant correlation between serum/plasma proteome profile and clinical parameters in FM patients, such as mechanical and thermal pain thresholds, pain intensity and psychological distress [21; 22; 64; 65].…”
Section: Discussionmentioning
confidence: 99%